Strategi Komunikasi Pemasaran Agrowisata Berbasis Ketahanan Pangan di Desa Renah Kayu Embun (RKE) Kecamatan Kumun Debai Kota Sungai Penuh - Rahayu, Silvia; Evanita, Susi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The purpose of this study is to analyze the marketing communication strategies for agritourism based on food security in Renah Kayu Embun Village, Kumun Debai Sub-district, Sungai Penuh City. The research method used is Participatory Rural Appraisal (PRA). Data were collected through interviews, observations, documentation, and Focus Group Discussions (FGD). The analysis was conducted interactively and included a SWOT analysis. The technique for selecting research informants was purposive sampling, involving 25 agritourism business actors focused on food security in Renah Kayu Embun Village, Kumun Debai Sub-district, Sungai Penuh City. The results of the study indicate that the village authorities have not yet been able to effectively manage the organization, marketing, promotion, business unit development, and partnerships. Consequently, there is a need for an integrated marketing communication model through the empowerment of food security-based agritourism in Renah Kayu Embun Village, Kumun Debai Sub-district, Sungai Penuh City.